Implementation of the Fuzzy Time Series Singh Method for Forecasting Non-Oil and Gas Export Values in Indonesia - Borahima, Maharani Safira B.; Sain, Hartayuni; Setiawan, Iman; Fadri, Firda (BERKALA SAINSTEK, 2024)
Export activities drive a country's economic growth by increasing revenue and strengthening trade relations between countries. In Indonesia, non-oil and gas products are the primary contributors of export performance. In 2022, non-oil and gas exports values reached 275.96 million USD, marking an increase of 25.80% compared to the previous year's export value. This growth in export value was influenced by various external factors, leading to substantial changes. The government requires further analysis to forecast future trends in non-oil and gas export values due to the uncertain and fluctuating patterns. The Singh Fuzzy Time Series method, an advancement of FST, utilizes fuzzy sets to forecast volatile economic data, yielding more accurate predictions. This research used the Singh FST method and achieved a low MAPE value of 1.31%, indicating a high level of accuracy. Forecasts for Indonesia's non-oil and gas export value over the next three months are projected to reach USD 22,263.02 million in January 2023, followed by USD 22,217.21 million in February 2023, and USD 22,243.68 million in March 2023. These export value forecasts can aid the government in policy-making related to exports and sustain the stability of the country’s economic growth rate.